PEMBERDAYAAN HOME INDUSTRY KERAJINAN BAMBU MENUJU KEMANDIRIAN - Muhammad Anshor; Nurlela Nurlela (LP3K Lampung, 2023)
This community service aims to improve the quality of human resources and lift the existence of UKM / Home Bamboo Crafts Industry in Sonobekel village. The availability of raw materials in this case bamboo is a driver of this small business to produce. Businesses that have been running have problems related to capital and marketing. So there needs to be empowerment that contains training to overcome these problems. The lack of capital can be overcome by providing pre-cooperative training and formation for craftsmen. Second, this marketing problem also concerns the creation of goods made / output. The more innovation and according to the needs of the times, the more orders for goods sold. This will open up new markets for the creative industry, especially bamboo crafts. So there is a need for innovation training to increase the value for bamboo crafts. The process of community empowerment needs to be carried out in stages, continuously and sustainably.